Implementasi Bahan Ajar Karakteristik Geografis Madura Berbasis Scientific Aproach untuk Siswa SD - Bagus Rahmad Wijaya; Aditya Dyah Puspitasari; Dzum Ma'isyatin Sahliyah (Musamus Journal of Primary Education, 2022)
The research aims to improve student learning outcomes by implementing teaching materials for geographical characteristics and the utilization of the potential of the Madura coast based on a scientific approach for elementary students. The subjects of this study were 24 4th grade students at SDN Tlanakan 1 Pamekasan. The method used is pre-experimental with a pre-test and post-test design. The research instrument used a cognitive learning outcome evaluation sheet. Furthermore, the data on student learning outcomes was tested for normality and homogeneity. Based on the results of normality analysis, it is known that the significance value in the pre-test and post-test is 0.081, and the degree of homogeneity is 0.073. After the data is known to be normal and homogeneous, it is tested using the t test with paired samples. Based on the results of the t-test, it is known that there is a difference between the pre-test and post-test values with a t-count value of -24.920 (the negative sign is not taken into account), which is greater than the t-table 2.069. The percentage of classical completeness also shows an increase in learning outcomes from the pre-test with a value of 0% to the post-test with a value of 87.5%. From the results of the study, it can be concluded that teaching materials are effective for improving student learning outcomes.